Identificação dos aspectos antropotecnológicos no Plano de Auxílio Mútuo (PAM) - Bail, Rosângela de França (2019)
Anthropotechnology studies the adaptation of the individual to the production process, emphasizing the complexity of the relationship between man, machine and technology, relating it to the well-being of the human being. This work aims to study how the anthropotechnological aspects are inserted in the Mutual Assistance Plan (PAM), compared to the North American Disaster Mutual Assistance (DMA), which works similar to the Brazilian project. WFP is a non-profit institution that seeks to establish and maintain interpersonal relationships and member interaction with federal, state, and municipal authorities responsible for responding to emergencies. The present study has as specific objectives: to identify the characteristics of anthropotechnology and the transfer of knowledge and technology (TCT), to describe the origin of the MAP, to establish a comparison between the MAP and the MAP and to look for the anthropotechnological evidences in the MAP. To reach these objectives, an exploratory bibliographical research was carried out, which adopted the strategy of systematic literature review. For the field research, data were collected from the PAM of Brazil and the State of Paraná, aiming to observe its origin, its evolutionary process and its main results. In the final field research, the case of PAM, in Ponta Grossa - PR, was studied in more detail. And the results show that anthropotechnology is linked to all the activities of WFP, be it in the industrial work environment, the training offered to employees, in interpersonal relationships, in the transfer of knowledge and technology in the actions of WFP, with partner companies and other participants.